The Management of Brain Metastases in Non-Small Cell Lung Cancer - Owen, Scott; Souhami, Luis (Frontiers in Oncology, 2014)
Brain metastases (BM) are a common and lethal complication of non-small cell lung cancer (NSCLC) which portend a poor prognosis. In addition, their management implies several challenges including preservation of neurological and neuro-cognitive function during surgery or radiation -therapy, minimizing iatrogenic complications of supportive medications, and optimizing drug delivery across the blood brain barrier (BBB). Despite these challenges, advancements in combined modality approaches can deliver hope of improved overall survival and quality of life for a subset of NSCLC patients with BM. Moreover, new drugs harnessing our greater understanding of tumour biology promise to build on this hope. In this mini-review, we revised the management of BM in NSCLC including advancements in neurosurgery, radiation therapy, as well as systemic and supportive therapy.